A new precise mass for the progenitor of the Type IIP SN 2008bk - Maund JR; Mattila S; Ramirez-Ruiz E; Eldridge JJ (OXFORD UNIV PRESS, 2025)
The progenitor of the Type IIP supernova (SN) 2008bk was discovered in pre-explosion g'r'i'IYJHK(s) images, acquired with European Southern Observatory Very Large Telescope FOcal Reducer and low dispersion Spectrograph, High Acuity Wide field K-band Imager and Infrared Spectrometer and Array Camera instruments and the Gemini Multi-Object Spectrograph-South instrument. The wealth of pre-explosion observations makes the progenitor of this SN one of the best studied, since the detection of the progenitor of SN 1987A. Previous analyses of the properties of the progenitor were hampered by the limited quality of the photometric calibration of the pre-explosion images and the crowded nature of the field containing the SN. We present new late-time observations of the site of SN 2008bk acquired with identical instrument and filter configurations as the pre-explosion observations, and confirm that the previously identified red supergiant (RSG) star was the progenitor of this SN and has now disappeared. Image subtraction techniques were used to conduct precise photometry of the now missing progenitor, independently of blending from any nearby stars. The nature of the surrounding stellar population and their contribution to the flux attributed to the progenitor in the pre-explosion images are probed using Hubble Space Telescope Wide Field Camera 3 Ultraviolet-Visible/Infrared observations. In comparison with MARCS synthetic spectra, we find the progenitor was a highly reddened RSG with luminosity log(L/L-circle dot) = 4.84(-0.12)(+0.10), corresponding to an initial mass of M-init = 12.9(-1.8)(+1.6)M(circle dot). The temperature of the progenitor was hotter than previously expected for RSGs (T similar to 4330 K), but consistent with new temperatures derived for RSGs using spectral energy distribution fitting techniques. We show that there is evidence for significant extinction of the progenitor, possibly arising in the circumstellar medium, but that this dust yields a similar reddening law to dust found in the interstellar medium (E(B - V) = 0.77 with R-V = 3.1). Our improved analysis, which carefully accounts for the systematics, results in a more precise and robust mass estimate, making the progenitor of SN 2008bk the most well understood progenitor of a Type IIP SN from pre-explosion observations.